Enhancing numeracy literacy through algebra learning materials: A vocational high school context - Hapsari, Tiara; Rif’at, Mohamad; Kusumastuti, Nilamsari (Universitas Islam Raden Intan Lampung, INDONESIA, 2025)
Purpose: This study aims to develop algebra teaching materials based on numeracy literacy to enhance vocational high school students’ understanding of mathematical concepts and their ability to solve contextual problems.Method: The research used a qualitative research and development approach following the ADDIE model, which includes five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews, expert validation sheets, questionnaires, and numeracy literacy tests administered to tenth-grade students.Findings: The analysis stage revealed that only 44 percent of students met the minimum standard of numeracy literacy. After the implementation of the developed materials, 71.8 percent of students achieved the Minimum Mastery Criteria (KKM), indicating improved performance. Expert validation yielded a score of 81.67, suggesting high validity. Students also gave positive responses, with average ratings of 80.67 percent for content, design, and language.Significance: The study demonstrates that algebra teaching materials designed through a structured development model and grounded in numeracy literacy can significantly improve student learning outcomes in vocational education. These materials help bridge the gap between theoretical concepts and real-world application, supporting national educational goals related to the Minimum Competency Assessment (AKM) and preparing students for professional environments.